Bài giải.
Cách làm của em chỉ nông dân thế này thôi, có gì chị giúp em sửa lại nhé!
Ta có : $7\left ( x-2004 \right )^2=23-y^2$
$=> 7\left ( x-2004 \right )^2+y^2=23$
Ta có : $|x-2004|$\leq 1 vì $7.2^2=7.4=28>23$
* Nếu $|x-2004|=1$
\Rightarrow $\left[\begin{matrix}x-2004=1\\
x-2004=-1\end{matrix}\right.$
\Rightarrow $\left[\begin{matrix}x=2005\\
x=2003\\
7.1^2+y^2=23\\
7.(-1)^2+y^2=23\end{matrix}\right.$
( vì từ đây 2 pt giống nhau nên giải 1 pt)
$=>7+y^2=23$
$=>y^2=23-7=16$
$=>y^2=4^2=\left ( -4 \right )^2$
$=>\left[\begin{matrix} y=4\\ y=-4\end{matrix}\right.$
Mà $x,y\in N$
\Rightarrow $(x;y)=(2005;4);(2003;4)$
* Nếu $x-2004=0$
$=>x=0+2004=2004$
$=>7.0^2+y^2=23$
$=>0+y^2=23$
$=>y^2=23-0=23$
$=>y\in \phi$
Vậy $(x;y)=(2005;4);(2003;4)$